KONSEP PENDIDIKAN ISLAM IMAM SUPRAYOGO: Transformasi UIN Maulana Malik Ibrahim Malang - Syafi'i, Ahmad (Pascasarjana IAIN Sorong, 2023)
The phenomenon of the dichotomy of science is increasingly troubling. Imam Suprayogo, behind the concept of Tarbiyah Ulu al-Albab, is a solution to the dichotomy of science by collaborating on science. This paper aims to: 1) describe the concept of education paradigma of the Qur'an, 2) describe the academic culture of Maulana Malik Ibrahim Islamic State University of Malang, and 3) The relevance concept of Imam Suprayogo's Islamic studies to the reality of Islamic studies in Indonesia. This paper is a literature research using content analysis techniques. The results of this study show that: 1) Tarbiyah Ulu al-Albab is an educational concept paradigma of the Qur'an with a dzikr, fikr, and amal shaleh approach, 2) The academic culture of the Maulana Malik Ibrahim Islamic State University of Malang campus displays; a) credible, compatible, and professional educators; b) a multifunctional mosque, not just as a symbol; c) ma'had like a boarding school; d) boarding school serves to form spirituality and morals; d) availability of libraries; e) laboratory; f) studying room; g) offices as a means of administrative services; h) arts and sports development centers; and i) as well as a broad and strong budget, 3) Imam Suprayogo's Islamic Studies Thought is very relevant to the reality of Islamic studies in Indonesia.